Underestimated and cryptic diversification patterns across Afro‐tropical lowland forests. (15th January 2019) - Huntley, Jerry W.; Keith, Katrina D.; Castellanos, Adrian A.; Musher, Lukas J.; Voelker, Gary
Abstract: Aim: Vertebrate diversity in the Guineo‐Congolian forests (GCF) of Africa is high, yet mechanisms responsible for generating that diversity remain remarkably understudied. These forests have alternatively been viewed as centres of diversification ("cradles") or more recently, as the opposite ("museums"). Here, we use a comparative dataset of avian and mammalian species to examine genetic diversification patterns across these forests and use these results to explain observed patterns in light of Plio‐Pleistocene climatic change and life‐history. Location: Africa. Methods: We analysed patterns of diversification across the GCF using a dataset composed of 629 and 1, 048 mitochondrial sequences from 60 avian and 36 mammalian species, respectively. Uncorrected pairwise genetic distances were compared at three distinct geographical levels: west versus east of the Dahomey Gap, among the three major forest blocks, and among seven historical refugial areas. The timing of diversification was assessed for passerines, Rodentia, and Chiroptera. Results: We found substantial signatures of diversification in all three levels of our geographical comparisons. We recovered substantial disparity in the amount and depth of structure of diversification patterns between low dispersers (understorey birds and rodents) and more capable dispersers (other bird species and bats). Additionally, our chronogram recovered recent speciation and intraspecific diversification across songbird and mammalian lineages. Main conclusions: The discrete, and often deep, structuring of genetic diversification for both birds and mammals across the GCF revealed strong correlations between historic landscape fragmentation and dispersal ability. Our results revealed a striking amount of unrecognized genetic diversity, which may be suggestive of cryptic species. Given the rate at which these forests are being negatively impacted by human intervention, our general lack of knowledge concerning vertebrate diversity across these forests may very well impact our ability to identify evolutionary processes underlying diversity and enact meaningful conservation efforts in the future.